2010
DOI: 10.1016/j.supflu.2010.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of phenol on glucose degradation during supercritical water gasification

Abstract: International audienceBiomass is the ideal alternative renewable energy that might help decrease CO2 emissions. Super Critical Water Gasification (SCWG) is a recent treatment method which is still being developed as regards wet biomass. Above its critical point, water has specific properties and is able to convert wet biomass into gas, and especially into hydrogen. In order to propose a general reaction scheme of the SCWG as regards the lignocellulosic biomass conversion, the interactions between lignin and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 42 publications
2
32
0
1
Order By: Relevance
“…Gasification and hydrogen production yields were lower than those calculated values which led the authors to suggest that even in real biomass, interactions between each component occurred. Similar results have been observed by other authors: Weiss-Hortala et al [61] observed a significant decrease in gas yields even when a small portion of phenol (a lignin decomposition compound) was blended with glucose. Goodwin and Rorrer [62] could not attain a 100% carbon gasification efficiency for xylose and phenol mixtures even at 750 °C.…”
Section: Mixturessupporting
confidence: 91%
“…Gasification and hydrogen production yields were lower than those calculated values which led the authors to suggest that even in real biomass, interactions between each component occurred. Similar results have been observed by other authors: Weiss-Hortala et al [61] observed a significant decrease in gas yields even when a small portion of phenol (a lignin decomposition compound) was blended with glucose. Goodwin and Rorrer [62] could not attain a 100% carbon gasification efficiency for xylose and phenol mixtures even at 750 °C.…”
Section: Mixturessupporting
confidence: 91%
“…Sawdust contains lignin, which is notorious in retarding 60) showed that gasification is inhibited by lignin in supercritical water using the batch-type reactor. Weiss-Hortala et al 61) showed that phenol, the main structure of lignin, retards glucose gasification in supercritical water. Without these manures, the homogeneous reaction can be expressed by a single straight line in the Arrhenius plot, with pre-exponential factor of 50.0 s -1 and activation energy of 67.9 kJ/mol.…”
Section: Determination Of Reaction Rate Constantmentioning
confidence: 99%
“…Many of these techniques have been repeatedly demonstrated in laboratory experiments to thoroughly destroy wet wastes such as sewage and oily sludges with efficiencies exceeding 99% (Cao et al, 2011). This high level of destruction is possible due to supercritical water's unique properties that change from standard phases, to allow for solvation of organic substances, diffusivity into solid materials and modified reactivity, leading to the degradation of organic substances into carbon dioxide, carbon monoxide, water, and thermal energy in a single reactor system (Byrd et al, 2008;Savage, 2009;Weiss-Hortala et al, 2010).…”
Section: Hydrothermal Decomposition and Conversionmentioning
confidence: 99%